2015
DOI: 10.1002/etc.2867
|View full text |Cite
|
Sign up to set email alerts
|

Planktonic and biofilm‐grown nitrogen‐cycling bacteria exhibit different susceptibilities to copper nanoparticles

Abstract: Proper characterization of nanoparticle (NP) interactions with environmentally relevant bacteria under representative conditions is necessary to enable their sustainable manufacture, use, and disposal. Previous nanotoxicology research based on planktonic growth has not adequately explored biofilms, which serve as the predominant mode of bacterial growth in natural and engineered environments. Copper nanoparticle (Cu-NP) impacts on biofilms were compared with respective planktonic cultures of the ammonium-oxidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…Yu et al [22] studied the toxicity of four widely used NPs (TiO 2 , SiO 2 , Ag and CdTe/CdS) to Chlamydomonas reinhardtii and found different cytotoxicity effects. Reyes et al [29] revealed that growth rate of A . vinelandii biofilms was significantly reduced as exposed to CuNPs.…”
Section: Resultsmentioning
confidence: 99%
“…Yu et al [22] studied the toxicity of four widely used NPs (TiO 2 , SiO 2 , Ag and CdTe/CdS) to Chlamydomonas reinhardtii and found different cytotoxicity effects. Reyes et al [29] revealed that growth rate of A . vinelandii biofilms was significantly reduced as exposed to CuNPs.…”
Section: Resultsmentioning
confidence: 99%
“…Differences between the three species' reactions were also related to species traits such as speed of growth and nutrient requirements. 140 In activated sewage sludge, nitrifying bacteria were compromised both in enzyme activity and abundance by SiO 2 NP, yet only at high concentration 126 (Table 3). García et al 9 observed that CeO 2 NP andconsiderably less -AuNP reduced the activity of ammonifying bacteria in a wastewater treatment plant, whereas no such effects were seen for TiO 2 -NP and AgNP.…”
Section: Ecosystem Functioningmentioning
confidence: 99%
“…In particular, biofilms are less restrained by antibacterial agents than the respective planktonic bacteria are. 8 Nanomaterials are materials that have at least one dimension (1-100 nm) in the nanometer scale range or whose basic unit in the three-dimensional space is in this range. 9 NPs in particular have demonstrated broad-spectrum antibacterial properties against both Gram-positive and Gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%